Olokizumab plus methotrexate: safety and efficacy over 106 weeks of treatment - Eugen Feist; Roy M. Fleischmann; Saeed Fatenejad; Daria Bukhanova; Sergey Grishin; Sofia Kuzkina; Michael Luggen; Evgeniy Nasonov; Mikhail Samsonov; Josef S. Smolen (Современная ревматология, 2024)
Objective. To report long-term safety and tolerability of olokizumab (OKZ) in combination with methotrexate (MTX) in subjects with active rheumatoid arthritis (RA), using pooled data from three randomised clinical trials (RCT) followed by open-label extension (OLE) study.Methods. Cumulative data from three phase 3 core trials and their OLE were analysed. Safety variables assessed included treatment-emergent adverse events (AEs), serious AEs (SAEs), AEs of special interest and laboratory results. Efficacy assessments included ACR20/50/70 responses, Disease Activity Score 28 (C-reactive protein) <3.2, CDAI remission and low disease activity (LDA), SDAI remission and LDA, HAQ-DI decrease of 0.22 unit and Boolean 2.0 remission.Results. A total of 2304 patients received OKZ in combination with MTX either once every 2 weeks or once every 4 weeks. Event rates per 100 patient-years in OKZ every 2 weeks and OKZ every 4 weeks, respectively, were 9.57 and 9.13 for SAEs; 2.95 and 2.34 for serious infections; 0.09 and 0.05 for gastrointestinal perforations; 0.58 and 0.83 for major adverse cardiovascular events; and 0.45 and 0.50 for malignancies. No increase in the rate of any AE was observed over 106 weeks of treatment. The evaluation of laboratory variables demonstrated the expected changes, like neutropenia, elevation of liver enzymes and blood lipids. Clinical response rates remained stable during the OLE.Conclusion. The long-term safety and tolerability of OKZ in combination with MTX remained stable. The efficacy of OKZ was maintained through week 106. These findings support OKZ as a treatment option for patients with active RA.